Kajian terhadap pengetahuan dan amalan pengurusan sisa pepejal dalam kalangan masyarakat di Taman Mesra dan Taman Bakti Kota Bharu, Kelantan - Ismail, Aslina (Universiti Sains Malaysia, 2012)
The rise in solid waste production has been a critical problem at present situation. This increase has been influenced by economic, population, and industry growth. Thus, the best way to control and reduce the production of solid waste is through the direct involvement of the society. Therefore, it is important to investigate the level of knowledge and application among the society with regards to solid waste management. The study conducted at Taman Mesra and Taman Bakti. Research sample size consists of 150 respondents (n=150). Research findings indicate that both occupants in the two residential areas have a level of knowledge of (64.7%) and application of (57.3%) in relations to solid waste management. From the results obtained, demographic attributes such as age, occupation and education level do not affect the level of knowledge and application within the society in Taman Mesra (p<0.05). However, demographic attributes such as occupation and education level affect the level of knowledge and application within the society in Taman Bakti (p>0.05). In contrast, age factor does not affect the level of knowledge and application within the society in between Taman Mesra and Taman Bakti (p>0.05). There is also a significant difference in the level of application among the society in Taman Mesra and Taman Bakti (p<0.0.5). In conclusion, in order to increase the awareness with regards to solid waste management, education and information should be improved among the societies.